Developing of STEM-based charta learning media to improve critical thinking ability student on plant structure and function material - Adrian Topano; Dondi Kurniawan; Ega Arya Saputra (University of Muhammadiyah Malang, 2023)
This research was motivated by several obstacles, including teachers in the learning process only focusing on thick textbooks and the student worksheets provided by the school were less interesting and effective. The aim of this research is to develop chart learning media based on Science Technology Engineering Mathematics (STEM) to improve critical thinking skills. This development research was carried out at Junior High School 7 of Bengkulu, Bengkulu Province - Indonesia using the Thiagarajan 4-D model which consists of four stages. The instruments used were media suitability validation questionnaires, teacher responses, student responses, and students’ critical thinking ability tests on STEM-based graphic media. Data from questionnaire analysis by calculating the percentage of achievement for each component is 86.6% (material expert), 100% (linguist), 98.75% (media/design expert), and 88.3% (test question expert) with the category suitable for use. The practicality of graphic learning media based on student response data and science teacher responses conducted in limited trials shows that STEM-based graphic learning media on Plant Structure and Function material includes very practical criteria for use without revision with percentages of 92, 80%, and 94%. The effectiveness of media has an important role and helps students develop their potential in the learning process. The conclusion of this research is that the media developed has been practically and effectively used as a learning medium in supporting the teaching and learning process on the structure and function of plants in improving the critical thinking skills of class VIII junior high school students.